Conjunctival microbiota variations in a subset of middle-aged and elderly individuals from Beijing, China - Tian-Yao Zhao; Yu-Chen Wang; Ying-Juan Sun; Jun-Yue Wang; Xiao-Dan Jiang; Xue-Min Li; Ai-Hua Deng (International Journal of Ophthalmology)
AIM: To isolate and identify the conjunctival microbiota of cataract patients and analyze the associated influencing factors. METHODS: This study recruited 216 participants (216 eyes) from April 2022 to July 2022. Under the condition of no antibiotic use prior to cataract surgery, sterile swabs were used to collect samples from the lower conjunctival sac. Bacterial cultures were then conducted, followed by species identification through 16S rDNA gene sequencing. Clinical factors associated with positive or negative bacterial isolation rates were analyzed, including age, gender, meibomian gland dysfunction (MGD), history of hypertension, history of diabetes, history of cancer, history of infectious diseases and the habit of wearing masks. RESULTS: Among the 216 eyes, 78 eyes yielded isolates, with an isolation rate of 36.11%, detecting a total of 122 strains. Gram-positive rods accounted for 49.18% (60 strains), gram-positive cocci accounted for 45.08% (55 strains), gram-negative bacteria accounted for 4.92% (6 strains), and fungi accounted for 0.82% (1 strain). This study found that the most abundant genera in the conjunctival sac were Corynebacterium (42.62%), Staphylococcus (31.15%), Micrococcus (9.84%), Acinetobacter (4.10%), and Bacillus (3.28%). Furthermore, age (P=0.006), gender (P=0.039), diabetes (P=0.003), history of infectious diseases (P=0.02), and duration of mask replacement (P<0.001) were important factors influencing the positive bacterial culture of the conjunctival microbiota. Although hypertensive patients exhibited a higher isolation rate of conjunctival bacteria, it did not reach statistical significance, and the history of cancer did not affect the isolation rate of the conjunctival microbial community in cataract patients before surgery. CONCLUSION: Potential changes are observed in the conjunctival microbiota among a sample of middle-aged and elderly individuals from Beijing, China. Notably, an increased isolation rate of Corynebacterium and Micrococcus is detected, suggesting a possible change in the microbial balance that requires further investigation and attention from the ophthalmological community. Advanced age, female gender, MGD, diabetes, a recent history of infectious diseases, and inadequate mask-wearing habits are potentially significant factors associated with the conjunctival microbiota. These factors should be considered in the development of strategies to prevent perioperative infections in cataract surgery patients.